Previous Creatinine Levels Safely Predict Amantadine Dose for Influenza a Outbreak Control - Jane A Buxton; Danuta M Skowronski; Helen Ng; Steve A Marion; Michele Williams; Anna Forbes; Arlene King; Jamie Hockin (Canadian Journal of Infectious Diseases)
BACKGROUND: Amantadine, an antiviral agent, is the only drug currently approved in Canada for prophylaxis of influenza A virus infection. To minimize side effects, the amantadine dose is adjusted for age and estimated creatinine clearance (CrCl) based on plasma creatinine (Cr) levels. As amantadine is used more frequently for influenza A outbreak control in care facilities for elderly people, physicians are increasingly called on to prescribe it for residents and to consider the necessity of requesting plasma Cr levels.